In vitro and molecular docking evaluation of black sesame seeds' anti-prostate cancer and antioxidant activity processed by nine steaming nine drying - Glennielyn D. Magdamit; Cheng-Yang Hsieh; Mon-Juan Lee; Kathlia A. De Castro-Cruz; Samantha Franchette B. Austria; Beatrice D. Sipat; Steven Kuan-Hua Huang; Po-Wei Tsai (Applied Biological Chemistry)
Abstract Black sesame seeds, known for their rich flavor and medicinal properties, hold significant potential as natural therapeutics against prostate cancer, a major health challenge for men today. This study explores the traditional processing technique of nine cycles of steaming and drying, which enhances the bioactive potential of these seeds. The impact of this processing on the antioxidant and anti-prostate cancer properties of black sesame seeds was systematically investigated, focusing on the key lignans, sesamin and sesamolin. HPLC was utilized to analyze the content ratios of sesamin and sesamolin, while DPPH and FRAP assays evaluated antioxidant capabilities, and MTT assays assessed anti-cancer properties against DU145 cells. Findings reveal that three cycles of steaming and drying significantly enhance antioxidant and anti-cancer activities against DU145, achieving peak concentrations of sesamin and sesamolin of 21.583% and 14.991%, respectively, with an optimal ratio of 1.4397:1. The superior antioxidant and anti-prostate cancer activity of this sample is attributed to optimal processing conditions that maximize the stability and extraction of bioactive compounds, particularly non-lignan antioxidants, while minimizing degradation; this is likely enhanced by the interplay between various phytochemicals and the effects of thermal processing on cellular structure. Processed seeds consistently outperformed raw seeds—except for those subjected to a single cycle. Additionally, molecular docking analyses revealed compelling interactions between sesamin and sesamolin and key proteins implicated in prostate cancer (FYN, ITGB3, PDGFRA, PDGFRB, and PIK3R1), demonstrating higher LibDock scores than the standard anti-cancer drug 5-fluorouracil. This research highlights the exceptional antioxidant and anti-cancer potential of black sesame seeds, particularly through the three-steaming and three-drying method, emphasizing the importance of the sesamin to sesamolin ratio in developing future anti-cancer therapeutics.